Altered Behaviors and Impaired Synaptic Function in a Novel Rat Model With a Complete Shank3 Deletion - Song, Tian-Jia; Lan, Xing-Yu; Wei, Meng-Ping; Zhai, Fu-Jun; Boeckers, Tobias M.; Wang, Jia-Nan; Yuan, Shuo; Jin, Meng-Ying; Xie, Yu-Fei; Dang, Wan-Wen; Zhang, Chen; Schön, Michael; et al. (Frontiers in Cellular Neuroscience, 2019)
Mutations within the Shank3 gene, which encodes a key postsynaptic density (PSD) protein at glutamatergic synapses, contribute to the genetic etiology of defined autism spectrum disorders (ASDs), including Phelan-McDermid syndrome (PMS) and intellectual disabilities (ID). Although there are a series of genetic mouse models to study Shank3 gene in ASDs, there are few rat models with species-specific advantages. In this study, we established and characterized a novel rat model with a deletion spanning exons 11 to 21 of Shank3, leading to a complete loss of the major SHANK3 isoforms. Synaptic function and plasticity of Shank3-deficient rats were impaired detected by biochemical and electrophysiological analyses. Shank3-depleted rats showed impaired social memory but not impaired social interaction behaviors. In addition, impaired learning and memory, increased anxiety-like behavior, increased mechanical pain threshold and decreased thermal sensation were observed in Shank3-deficient rats. It is worth to note that Shank3-deficient rats had nearly normal levels of the endogenous social neurohormones oxytocin (OXT) and arginine-vasopressin (AVP). This new rat model will help to further investigate the etiology and assess potential therapeutic target and strategy for Shank3-related neurodevelopmental disorders.